Cariologic Study of the Plant Species on the South-Western Gutai Mountains Pasture - Zorica Voşgan; Roxana Vidican; Lucia Mihălescu; Monica Marian; Stela Jelea; Oana Mare Roşca; Anca Domuţa (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Agriculture, 2016)
This paper presents karyology aspects of the diploid and polyploid species frequency on the mountain pastures in the southwestern Gutai Mountains as well as the calculation of the diploid index. The phytocoenosis of the five plant associations identified on pasture were studied: Violo declinatae-Nardetum, Simon 1966, Agrostietum stoloniferae, (Ujvárosi 1941) Burduja et al. 1956, Scirpetum sylvatici, Ralski 1931, Maloch 1935 em. Schwick 1944, Calthetum laetae, Krajina 1933, Campanulo abientinae-Vaccinietum myrtilli, (Buia et al. 1962) Boşcaiu 1971. Karyotypes were taken for all encountered vegetal species to achieve an accurate cytoaxonomic analysis. The frequency of polyploid species was found in the five vegetal associations that were identified and studied in karyology terms. The number of polyploids, comprised between 52.94-75%, is ahead of the diploids number comprised between 25-43,75%, in the vegetal associations phytocoenosis of the mountainous region. Diplo-polyploid plants and those with an unknown karyotype have lower participation. The calculated value of the diploid index decreases with the increasing of the altitude, with subunit values between 0.33 - 0.82. Diploid index (DI) indicates instable character of vegetal formations of above-mentioned area, reflecting completely station conditions of the grassland. The genetic structure of the phytocoenosis and vegetal associations studied seen from the perspective of karyotypes, indicates a drop in the dioloid index value with the increasing of the anthropo- zoogen factor (excessive grazing).